Peningkatan Keterampilan Menulis Tegak Bersambung Melalui Metode Pembelajaran Drill di Kelas II Sekolah Dasar - Risna Aruna; Muhammad Ismail Sriyanto; Matsuri Matsuri (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2023)
The purpose of this research is to improve the cursive handwriting skill through drill learning method of the students in 2nd grade of SDN Soropadan No. 108 Surakarta. Classroom action research was used for this study, which was conducted over the course of two cycles. Every cycle had two meetings. Students in 2nd grade of SDN Soropadan No. 108 Surakarta was the subject of this research. They were 32 total students. The data was collected by observation, interview, test, and documentary. The data validity was using Â content validity, source triangulation and technique triangulation. The data analysis was using interactive analysis model. According to research results, the students in 2nd grade of SDN Soropadan No. 108 Surakarta saw an improvement in their cursive handwriting skills. When compared to the minimum guaranteed score of 75, the pre-action average for the cursive handwriting skills test was 57.03, with a classical completion rate of 16%, or as many as 5 out of 32 students. In the first cycle, the average value was 75.4, with a classical completion rate of 56%, or 18 out of 32 students, being successful. In the second cycle, the average value increased to 85.77, with classical completeness reached 84%, or 27 out of 32 students successfully completed. The conclusions in this research is cursive handwriting skill can be improved through drill learning method of the students in 2nd grade of SDN Soropadan No. 108 Surakarta.